DYSPLASIA OF THE HEART CONNECTIVE TISSUE AMONG CHILDREN - E.N. Basargina ("Paediatrician" Publishers LLC, 2008)
Dysplasia of the heart connective tissue among children includes atrioventricular valve prolapse, abnormally positioned cords, aneurysms of the interatrial septum. Dysplasia of the heart connective tissue draws steadfast attention of the pediatricians due to the high population recurrence and risks, leading to such complications, as mitral regurgitation, cardiac rhythm disturbances and in some cases fatal outcome. Among probable pathogenetimechanisms of dysplasia development, researcher considers magnesium ion deficiency. Based on the analysis of literature and own data, she draws a conclusion that it is effective and expedient to apply magnesium orotat (magnerot) among children for the correction of the collagen (accounted for dysplasia) metabolism disorders. Magnesium orotat based therapy among children, suffering from dysplasia of the heart connective tissue, reduces the indications of the valve prolapse, recurrence of mitral regurgitation, intensity of the clinical manifestations of the vegetative dysfunction, recurrence of the arrhythmias and is accompanied by the increase of the endoglobular magnesium level.Key words: children, dysplasia of the heart connective tissue, treatment, magnesium orotat.